8 Felo Perdana UMP Protege appointed to serve with management - Nor Salwana, Mohammad Idris (2022)
PEKAN, 5 October 2022 - A total of eight graduates of Universiti Malaysia Pahang (UMP) were selected in the Felo Perdana UMP Protege programme which will serve at UMP and be placed for six months to the university management including the Chairman of the UMP Board of Directors, Tan Sri Dato’ Sri Dr. Abdul Aziz Abdul Rahman.